2019
DOI: 10.1002/dvdy.89
|View full text |Cite
|
Sign up to set email alerts
|

Targeted exome sequencing reveals a novel GLI3 mutation in a Chinese family with nonsyndromic polydactyly

Abstract: Background Polydactyly is a phenotypically and genetically highly heterogeneous limb malformation with preaxial, postaxial, and central subtypes. The aim of this study was to identify genetically pathogenic factor in a Chinese nonsyndromic polydactyly family. Results Seven family members and 100 healthy controls were recruited, and the genetically pathogenic factor of the polydactyly family was investigated by targeted exome sequencing. Targeted exome sequencing revealed a novel frameshift mutation c.2148delA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…It has been demonstrated that GLI3 possesses a dual function, including a transcriptional activator of SHH signaling pathway by phosphorylated full‐length GLI3 and a repressor by C‐terminally truncated CLI3. Recently, several novel mutations of GLI3 have been identified in the patients with PD, including mutation c. 1622C > T (Zou et al, 2019), c.2148delA (Zhao, Xu, Liu, & Li, 2019), c.3437_3453delTCGAGCAGCCCTGCCCC, and c.3997C > T (Chen et al, 2019), c.1180C > TT (Ni et al, 2019). Therefore, our results suggested that this frameshift mutation of GLI3 might be a main reason for preaxial PD type IV phenotype in this Chinese family.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that GLI3 possesses a dual function, including a transcriptional activator of SHH signaling pathway by phosphorylated full‐length GLI3 and a repressor by C‐terminally truncated CLI3. Recently, several novel mutations of GLI3 have been identified in the patients with PD, including mutation c. 1622C > T (Zou et al, 2019), c.2148delA (Zhao, Xu, Liu, & Li, 2019), c.3437_3453delTCGAGCAGCCCTGCCCC, and c.3997C > T (Chen et al, 2019), c.1180C > TT (Ni et al, 2019). Therefore, our results suggested that this frameshift mutation of GLI3 might be a main reason for preaxial PD type IV phenotype in this Chinese family.…”
Section: Discussionmentioning
confidence: 99%
“…Shh signaling is mediated by three Gli genes in vertebrates (Gli1, Gli2, and Gli3). Of these, Gli3 is essential for limb development, as evidenced by the polydactylous phenotype of the extra-toes ( Xt ) Gli3 mutant allele [ 15 ]. Interestingly, it has been recently shown that Gli3 and HoxD12 interact both genetically and physically to modulate the function of Gli3R.…”
Section: Introductionmentioning
confidence: 99%